Dialogues with Tradition: Feminist-Queer Encounters in German Crime Stories at the Turn of the Twenty-First Century - Faye Stewart (Studies in 20th & 21st Century Literature, 2011)
Pieke Biermann’s feminist crime collection Mit Zorn, Charme, und Methode (1992) and Lisa Kuppler’s gay and lesbian anthology Queer Crime (2002) engage in a common project, the rewriting of a popular genre to give voice to previously marginalized identities and perspectives. This article investigates the ways in which each volume negotiates the gendered conventions of crime fiction and its subcategories, feminist and queer crime. A comparative analysis of three mysteries from each collection demonstrates the converging and diverging tendencies of feminist and queer representation in turn-of-the-twenty-first century crime narratives. Feminist mysteries by Edith Kneifl, Birgit Rabisch, and Barbara Neuhaus shift generic conventions by aligning narrative perspectives with a feminist world view that destabilizes male-dominated structures through the intervention of a strong female figure who successfully closes the case. By contrast, queer mysteries by Thea Dorn, Ursula Steck, and Susanne Billig destabilize generic conventions and structures of identity altogether, highlighting misreadings and unsolved mysteries through parody, double entendre, and open endings.
Keywords: Pieke Biermann; Feminism; Mit Zorn; Charme; und Methode; Lisa Kuppler; Queer Crime; gay; lesbian; marginalized identities; gendered conventions; crime novel; gender; queer; queer crime; crime narratives; 21st century; twenty-first century; Edith Kneifl; Birgit Rabisch; Barbara Neuhaus; male-dominated; Thea Dorn; Ursula Steck; Susanne Billig; misreadings; unsolved mysteries; German crime stories